2019
DOI: 10.1016/j.omtn.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

SDM6A: A Web-Based Integrative Machine-Learning Framework for Predicting 6mA Sites in the Rice Genome

Abstract: DNA N6-adenine methylation (6mA) is an epigenetic modification in prokaryotes and eukaryotes. Identifying 6mA sites in rice genome is important in rice epigenetics and breeding, but non-random distribution and biological functions of these sites remain unclear. Several machine-learning tools can identify 6mA sites but show limited prediction accuracy, which limits their usability in epigenetic research. Here, we developed a novel computational predictor, called the Sequence-based DNA N6-methyladenine predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(77 citation statements)
references
References 80 publications
(164 reference statements)
0
77
0
Order By: Relevance
“…The sensitivity, specificity and accuracy (Basith et al, 2019;Manavalan et al, 2018aManavalan et al, ,c, 2019a was applied to evaluating the performance of prediction methods. Here, HCC samples were regarded as positive samples; CwoHCC samples were negative samples.…”
Section: Performance Metricsmentioning
confidence: 99%
“…The sensitivity, specificity and accuracy (Basith et al, 2019;Manavalan et al, 2018aManavalan et al, ,c, 2019a was applied to evaluating the performance of prediction methods. Here, HCC samples were regarded as positive samples; CwoHCC samples were negative samples.…”
Section: Performance Metricsmentioning
confidence: 99%
“…(1) SDM6A: A sequence-based two-layer ensemble approach for the effective prediction of 6mA novel putative sites and non-6mA sites in the rice genome using Integrative Machine-Learning Framework [83]. (2) SNNRice 6mA: Another 6mA identification method for the rice genome using a simple and lightweight deep learning model and the evaluation based on five metrics like accuracy, sensitivity, specificity, Matthews correlation coefficient (MCC), and area under the curve (AUC)) [84].…”
Section: Bioinformatic Analysis Tools For 6mamentioning
confidence: 99%
“…Next, we further explore the potential molecular mechanism of up-regulated expression of MAPK4 in ALI. Recent decades, DNA methylation is commonly invoked as a mechanism for transcriptional repression [27][28][29], we wondered whether DNA demethylation of CpG island in MAPK4 promoter enhanced the expression of MAPK4 in LPS-induced ALI. Expectedly, bioinformatics analysis indicated that there was a CpG island in the promoter of MAPK4 ( Figure 6A).…”
Section: Nfkb1 and Nr3c1 Negatively Regulate The Expression Of Mapk4mentioning
confidence: 99%